2021
DOI: 10.1016/j.jot.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte ferroptosis contribute to the progression of osteoarthritis

Abstract: Summary Background Osteoarthritis (OA) is a complex process comprised of mechanical load, inflammation, and metabolic factors. It is still unknown that if chondrocytes undergo ferroptosis during OA and if ferroptosis contribute to the progression of OA. Materials and methods In our study, we use Interleukin-1 Beta (IL-1β) to simulate inflammation and ferric ammonium citrate (FAC) to simulate the iron overload in vitro . Also, we u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
185
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 224 publications
(195 citation statements)
references
References 42 publications
10
185
0
Order By: Relevance
“…Our findings in vitro prompted us to further analyse the function of HIF‐2α downregulation in D‐mannose‐induced chondrocyte resistance to ferroptosis and OA progression in vivo. Consistent with previous studies which indicated the role of chondrocyte ferroptosis in OA progression, 9 , 10 immunofluorescence staining described above revealed a striking reduction of the key ferroptosis inhibitor, GPX4, in the articular chondrocytes upon ACLT surgery (Figure 3A ). To examine whether D‐mannose‐induced inhibition of HIF‐2α would protect osteoarthritic cartilage by suppressing chondrocyte ferroptosis, we fed mice with D‐mannose solution or water as previously described and then performed ACLT surgery.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings in vitro prompted us to further analyse the function of HIF‐2α downregulation in D‐mannose‐induced chondrocyte resistance to ferroptosis and OA progression in vivo. Consistent with previous studies which indicated the role of chondrocyte ferroptosis in OA progression, 9 , 10 immunofluorescence staining described above revealed a striking reduction of the key ferroptosis inhibitor, GPX4, in the articular chondrocytes upon ACLT surgery (Figure 3A ). To examine whether D‐mannose‐induced inhibition of HIF‐2α would protect osteoarthritic cartilage by suppressing chondrocyte ferroptosis, we fed mice with D‐mannose solution or water as previously described and then performed ACLT surgery.…”
Section: Resultssupporting
confidence: 92%
“…Recent evidence has indicated that chondrocyte ferroptosis contributes to chondrocyte homeostasis and osteoarthritic cartilage degeneration. 9 Similar to previous study, ferrostatin‐1 (Fer‐1), the inhibitor of ferroptosis, could attenuate the cytotoxicity of IL‐1β to chondrocytes, indicating the existence of ferroptosis in IL‐1β‐treated chondrocytes (Figure S2 A). GPX4 is a canonical glutathione‐based ferroptosis inhibitor and functions mainly through inhibiting the formation of lipid peroxides.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…In the present research, a highly selective inducer of iron overload, ferric ammonium citrate (FAC), was used to establish an iron overload model in porcine oocytes. FAC, a trivalent iron salt, is absorbed in vivo by reducing trivalent iron to divalent ferrous iron (Cotticelli et al, 2019;Yao et al, 2021). It has been shown that FAC-induced intracellular iron overload causes ferroptosis (Fang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%